Penerapan RBAC pada Aplikasi WiFi Analyzer Android untuk Manajemen Akses PT Info Solusindo Data Utama - Muhamad Fauzi; I Made Sugi Ardana (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
This research discusses the implementation of the Role-Based Access Control (RBAC) method in an Android-based WiFi Analyzer application to enhance the security and efficiency of user access management in wireless network environments, addressing the difficulty technicians face in performing rapid network troubleshooting. The system was developed using the Scrum method and evaluated through Black Box Testing and User Acceptance Testing (UAT) involving 7 respondents across 4 evaluation indicators. RBAC was implemented to regulate access rights according to user roles (Developer, Admin, Subscriber), while the application's features include internet/intranet connection testing, signal strength analysis (RSSI), and best channel allocation recommendations. Black Box Testing results show that RBAC was 100% successful in dynamically restricting access rights based on user roles. UAT results, based on 70 total responses, show 92.9% positive ratings (61.4% Strongly Agree, 31.4% Agree), while 7.1% rated Disagree on indicators related to data reading speed and visualization display, with no Strongly Disagree responses recorded. These results demonstrate that the application effectively helps Engineers On Site analyze problems and adjust WiFi channels quickly and safely, although certain visualization aspects still require further refinement.